Circ_0072088 promotes the development of non‐small cell lung cancer via the miR‐377‐5p/NOVA2 axis - Zhaofeng Tan; Fang Cao; Bin Jia; Lei Xia (Thoracic Cancer, 2020)
Background Non‐small cell lung cancer (NSCLC) is one of the leading causes of cancer‐related death globally. This study aimed to disclose the role of circular RNA circ_0072088 in NSCLC and illustrate its potential mechanism. Methods Quantitative real‐time polymerase chain reaction (qRT‐PCR) was applied to detect the expression of circ_0072088, zinc finger RNA binding protein (ZFR), microRNA‐377‐5p (miR‐377‐5p) and NOVA alternative splicing regulator 2 (NOVA2). The viability, colony formation, cell cycle, migration and invasion of NSCLC cells were measured by cell counting kit‐8 (CCK8) assay, colony formation assay, flow cytometry, wound healing assay and transwell invasion assay. Western blot assay was employed to examine the protein levels of proliferating cell nuclear antigen (PCNA), Cyclin D1, matrix metallopeptidase 2 (MMP2), MMP9 and NOVA2. The downstream targets of circ_0072088 and miR‐377‐5p were searched through using circular RNA Interactome and TargetScan databases, and the interaction between miR‐377‐5p and circ_0072088 or NOVA2 was confirmed by dual‐luciferase reporter assay and RNA immunoprecipitation (RIP) assay. in vivo tumor growth assay was used to evaluate the functions of circ_0072088 in the progression of NSCLC in vivo. Results GSE101586 dataset and the analysis of tissue specimens showed that circ_0072088 was aberrantly upregulated in tumor tissues of lung cancer and NSCLC. Circ_0072088 interference caused marked suppression on the proliferation and motility of NSCLC cells. Circ_0072088 could negatively regulate miR‐377‐5p through direct combination. Circ_0072088 contributed to the progression of NSCLC through sponging miR‐377‐5p. MiR‐377‐5p could directly interact with NOVA2, and the overexpression of NOVA2 overturned miR‐377‐5p‐mediated influence on NSCLC cells. Circ_0072088 facilitated the progression of NSCLC in vivo. Conclusions Circ_0072088 facilitated the proliferation and metastasis of NSCLC cells through upregulating NOVA2 via functioning as a competitive endogenous RNA (ceRNA) for miR‐377‐5p.